Guiding school improvement with action research - Sago, Richard; Association for Superdivision and Curriculum Development (Alexandria, Virginia : Association for Superdivision and Curriculum Development, 2000)
This video focuses on practical examples of how school administrators and teachers have benefit from their understanding of the action research process, becoming more reflective practitioners, progres they have made on schoolwide priorities and building more professional culture among faculty members
This program is based on the ASCD Book'Guiding School Improvement'
Title from title screen
Keywords: Action research in education -- United States; School improvement programs -- United States